Znaczenie sektora małych i średnich przedsiębiorstw w transformacji systemu gospodarczego - Murawiak, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The main reason for economic disproportion between countries depends on differences in institutional framework. They result from political system that can be shaped by externally imposed factors as in Poland until 1989 or free market conditions as in Poland since 1989. Such dependency has crucial impact on development of small and medium-sized enterprises SME – the main basis of changes in developing countries. The aim of the article is to analyse the importance of SME sector in an economy in transition. In this aspect, it is important to pay attention not only to growth but also to the development of SME. The article underlines that countries in transition have a lot in common. SME sector operates in more and more difficult conditions all over the world. Observing new tendencies in global economy, competitiveness of domestic enterprises does not depend on enterprises solely, but on more complex and mutually combined factors on the international level. The fi ndings suggest that the evolution of economic behaviour among enterprises is needed together with changes in economic policy conducted nationally and regionally.
Keywords: system ekonomiczny; transformacja; małe i średnie przedsiębiorstwa; Polska